Media Pembelajaran Perspektif Q.S Al-Baqarah Ayat 31 serta Implikasinya Terhadap Pendidikan - Faiz Aswa Nazhan; Cucu Surahman; Elan Sumarna; Restu Rizki Amanda; Rifqi Fathan Saepudin Muzakki (Mu'allim, 2025)
Learning Media has an important role when the teaching and learning process takes place. Learning media can make it easier for teachers to convey teaching material and make it easier for students to understand the material. However, there are still teachers who ignore and pay little attention to this matter. This research aims to explore learning media in Q.S al-Baqarah verse 31. This research uses a library study method, by examining four books of tafsir, as well as various books, scientific articles and other relevant references. The research results show that in Q.S al-Baqarah verse 31 there are at least two learning media (visual media and audio media) that Allah used when teaching Prophet Adam a.s. This media acts as an intermediary tool that can help improve student understanding and make learning more fun and interactive.